THE EFFECT OF INDIVIDUAL COUNSELING SERVICES WITH AN APPROACH RATIONAL EMOTIVE BEHAVIOR THERAPY (REBT) TO REDUCE CHILDREN'S FEELINGS OF LONELINESS IN ORPHANAGES - sri, sriintan; Putri Harahap, Ade Chita (Universitas Al-Hikmah Indonesia, 2024)
Adolescence is a transition from childhood to adulthood. At this stage of development, the younger generation must master social growth which is one of the tasks of development. When adolescents are unable to complete these developmental tasks, they feel rejected, alienated, and even equal. Children in orphanages also feel this loneliness. It's not uncommon for loneliness to make people think irrationally. REBT views equality as a result of individuals' irrational thinking. This type of research is pre-experimental research using a one group pretest and posttest design. Subjects were selected using the purposive sampling method. The subjects of this research were 5 (five) children from an orphanage with a high level of loneliness. The instrument used is a scale equivalent to the Likert scale model. Data were collected and processed using the non-parametric statistical technique Wilcoxon Signed Ranks Test with SPSS. In the validity and reliability test of the 20 statement items, there were 16 statement items that were valid for use with the result of the r table value at the 5% significance level being 0.2353, where the item could be said to be valid if the calculated r was > than r table. Furthermore, in the reliability test using the SPSS program, Cronbrach Alpha data was obtained with a value of 0.661, which is if the Cronbrach Alpha value is greater than 0.05 (0.661>0.05). The results of this study indicate that the significant value of asymp. signature. (2-tailed) < 0.05, namely 0.039. Thus, it is concluded that individual counseling services using the REBT approach are effective in reducing feelings of loneliness for children in orphanages.